2011
DOI: 10.1103/physreva.84.039907
|View full text |Cite
|
Sign up to set email alerts
|

Publisher’s Note: Quantum Fisher information of the Greenberger-Horne-Zeilinger state in decoherence channels [Phys. Rev. A84, 022302 (2011)]

Abstract: Publisher's Note: Quantum Fisher information of the Greenberger-Horne-Zeilinger state in decoherence channels [Phys. Rev. A 84, 022302 (2011)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 0 publications
0
64
0
Order By: Relevance
“…Such unitary process of equation (5) may be used to model the two-mode optical interferometry and the general Ramsey interferometry [8,36]. With equation (5), the QFI with respect of ϕ can be expressed in the following form [19,37,38,39,40]…”
Section: Quantum Fisher Informationmentioning
confidence: 99%
“…Such unitary process of equation (5) may be used to model the two-mode optical interferometry and the general Ramsey interferometry [8,36]. With equation (5), the QFI with respect of ϕ can be expressed in the following form [19,37,38,39,40]…”
Section: Quantum Fisher Informationmentioning
confidence: 99%
“…On the other hand , however, interaction between a system and an environment is unavoidable in reality, and the quantum decoherence induced by such interactions may decrease the QFI and destroy the quantum entanglement in the probe system exploited to improve the precision. In this regard, It has been shown that the interaction between a system and an environment usually makes the measurements noisy, which in turn degrades the estimation precision [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…This form of parameterization process is typical in interferometers. For instance, in a Ramsey interferometer H can be a collective angular momentum operator J n [27], which can be viewed as a generator of SU(2). In Mach-Zehnder interferometers, denoting a i and a † i (i=1,2) as the annihilation and creation operators for i th mode, then H can be (1) the photon number difference between two modes:…”
Section: Qfi For Unitary Parameterized Dynamicsmentioning
confidence: 99%
“…Quantum Fisher information (QFI) is another significant concept in quantum metrology and has been studied widely [20,21,22,23,24,25,26,19,27,28,29]. As an extension of the classical Fisher information in statistics and information theory, QFI plays a paramount role in quantum estimation theory.…”
Section: Introductionmentioning
confidence: 99%